Bubble point determination for CO2 + Ethanol + Alkanolamines (Monoethanolamine, Diethanolamine, or Triethanolamine) at high pressures - Brito Guerra Neto, Dival de (2014)
Experimental data from the phase transition of the ternary systems {CO2(1) + [0.25 monoethanolamine(2) + 0.75 ethanol(3)]}, {CO2(1) + [0.25 diethanolamine(2) + 0.75 ethanol(3)]} and {CO2(1)+ [0.25 triethanolamine(2) + 0.75 ethanol(3)]} is reported. A variable volume cell was employed using the static synthetic method in a temperature range of (313–343) K, pressures up to 14 MPa and CO2 mole fractions between 0.05 and 0.35. For xCO2 > 0.35 phase transition data could not be measured for pressures up to 35 MPa. Vapor–liquid transitions (VLE) of bubble point (BP) are determined for the three ternary systems studied. The determination of measures of the phase equilibrium of systems involving CO2 and alkanolamines are of great importance in the development of absorption processes. A great feature of alkanolamines is the possibility of capturing carbon dioxide (CO2) and promoting separation of this gas from other gas streams.